PENGARUH TENUR AUDIT, UKURAN PERUSAHAAN DAN ROTASI AUDIT TERHADAP KUALITAS AUDIT - Ririn Dwi Lestari, 13.05.52,0004; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2018)
Audit quality is related to qualification of expertise, timeliness of completion of work, adequacy of competent examination evidence at the lowest cost and independensin attitude with clients. This study aims to analyze the influence of auditing, firm size and audit rotation on audit quality. The population in this study is manufacturing companies listed on the Stock Exchange with period 2013 to 2015 of 149 companies. By using side purposive sampling technique, the sample is obtained by 67 companies. The analysis tool used is logistic regression. The result of the research shows that audit work has a significant negative effect on audit quality, meaning that the longer engagement done by companies in choosing KAP that can be invited to work together, causing the decrease of independence and objectivity due to excessive intimacy, will further decrease the quality of audit. While firm size and audit rotation have a significant positive effect on audit quality.Keywords: Audit management, firm size, audit rotation and audit quality